Phenotypic and molecular characterization of IMP-producing Enterobacterales in Spain: Predominance of IMP-8 in Klebsiella pneumoniae and IMP-22 in Enterobacter roggenkampii - Cañada-García, Javier E.; Grippo, Natalin; de Arellano, Eva Ramírez; Bautista, Verónica; Lara, Noelia; Navarro, Ana María; Cabezas, Teresa; Martínez-Ramírez, Nora Mariela; García-Cobos, Silvia; Calvo, Jorge; Cercenado, Emilia; Aracil, Belén; et al. (Frontiers in Microbiology, 2022)
Objectives Little is known about IMP-producing Enterobacterales (IMP-Ent) in Europe. We analyzed at genomic and phenotypic level IMP-Ent isolates circulating in Spain in a 9-year period. Materials and methods IMP-Ent isolates submitted to our reference laboratory were included. Antibiotic susceptibility was performed using microdilution method (EUCAST), and IMP-carbapenemase activity was measured with carbapenemase inhibitors, the β-CARBA method, the modified Hodge test (MHT), and the modified carbapenemase inhibition method (mCIM). All isolates collected were sequenced for high-resolution single-nucleotide polymorphism (SNP) typing, core genome multilocus sequence typing (cgMLST), and resistome analysis. Results Fifty IMP-Ent isolates, collected from 19 hospitals in 13 Spanish provinces, were detected: Klebsiella pneumoniae (IMP-Kpn) (24; 48%), Enterobacter roggenkampii (13; 26%), Enterobacter hormaechei (8, 16%), Klebsiella oxytoca (two; 4%), Enterobacter asburiae (one, 2%), Serratia marcescens (one; 2%) and Escherichia coli (one; 2%). All isolates were positive by the MHT and β-CARBA tests; 48 (96%) were mCIM positive; 12 (24%) and 26 (52%) displayed positive inhibition with dipicolinic (meropenem) and EDTA (ertapenem), respectively. Five IMP-carbapenemase types were identified: IMP-8 (22; 44%), IMP-22 (17; 34%), IMP-13 (7; 14%), IMP-28 (two; 4%), and IMP-15 (two; 4%), predominating IMP-8 in K. pneumoniae and IMP-22 in E. roggenkampii. IMP-28 was exclusively identified in K. oxytoca and IMP-15 in E. hormaechei. Predominant STs were ST405 (29.2%), ST15 (25%) and ST464 (20.8%) in IMP-Kpn; ST96 (100%) in E. roggenkampii and ST182 (62.5%) in E. hormachei. Colistin and amikacin were the most active non-carbapenem antibiotics against IMP-Ent. Conclusion IMP-Ent isolates remain infrequent in Spain, although in recent years have been circulating causing nosocomial outbreaks, being IMP-8-producing K. pneumoniae and IMP-22-producing E. roggenkampii the most frequently detected in this study. Inhibition with EDTA or dipicolinic acid presented false negative results in some IMP-producing strains. Active microbiological and molecular surveillance is essential for a better comprehension and control of IMP-Ent dissemination.